Drama: Guidelines for Teachers of Students with Mild General Learning Disabilities - O'Sullivan, Carmel (National Council for Curriculum and Assessment, 2003)
The approach advocated in the Primary School Curriculum, Drama constitutes a broadening in focus from the concept of drama as a performance-orientated activity towards the use of drama as a learning and developmental experience. Through a process of collaboration, and exploring a range of human feelings, drama can help students to explore a variety of social situations and moral questions within a supportive framework. In this way, drama can enable students to gain confidence in making decisions and in solving problems.
PUBLISHED
Dublin, National Stationery Office
Keywords: Creative Arts Practice; Identities in Transformation; Inclusive Society; Arts in Education; Autistic Spectrum disorders; Chronic Health Condition; Emotional-behavioural Problems; Intellectual Disability; Sensory impairment; Specific learning difficulties; Accessibility; Children; Education; Social participation